Motivation as a strategy to develop the listening skills outside the classroom in eighth grade students. - Espinoza Espinoza, Irene Rocío (Machala : Universidad Técnica de Machala, 2016)
This research is focused in the use of strategies to develop the listening skill in the students. this article analyzes the existing problems in students of eight years of basic education, because we have noted some of the factors that obstruct students learning. the main fact is that english teachers do not have strategies to motivate students to participate in activities, in a way to strengthen the ability to develop a complex skill, it produces discouragement among students to work on this listening skill. the main purpose of this research is to present strategies to awake the interest in the teachers to perform listening activities outside the classroom. the listening skill is very important in the teaching-learning process, so teachers must enhance their knowledge involving the implementation of good strategies for the development of listening skill and also to enhance the teacher-student relationship, it will create a more appropriate environment for the assimilation and retention of the information provided by teacher, which will result in meaningful learning. it is good to show teachers that there are a great set of motivational strategies to enhance the listening skill in the students, and eliciting the interest to extra-lessons. in that way they can do tasks without difficulties avoiding traditional teaching and promoting an interesting and fun teaching, in which the student is the main actor and performer of the activities planned by teacher. the benefits of this work are for teachers and students that are the main actors in the teaching-learning process.
Keywords: STUDENT PROBLEM; STRATEGY; LISTENING SKILL; TEACHER; STUDENT